Examining Character Structure and Function Across Childhood and Adolescence. Issue 4 (19th January 2018) - Shubert, Jennifer; Wray‐Lake, Laura; Syvertsen, Amy K.; Metzger, Aaron
Abstract : Character strengths are an integral component of positive youth development that can promote flourishing. Developmental principles posit constructs become increasingly complex with age, yet this process has not been examined with character. Using a socioeconomically and ethnically diverse sample of 2, 467 youth ages 9–19, bifactor models were estimated across elementary, middle, and high school‐age groups to examine age differences in character structure and function. With successive age, a greater number of specific character strength factors were identified, suggesting character structure becomes more differentiated across adolescence. Results linking character bifactor models to indicators of positive functioning also supported differentiation in character function across ages. Findings point to the need for theoretical and empirical considerations of character structure and function across development.